Interpretation of Tawhid Rububiyah in the Qur'an Surah Al-Fatihah: Study of Tafsir Ijmali - Muhammad Firman; Muhammad Frandika; Zulkifli; Edi Hermanto (Aslim: Journal of Education and Islamic Studies, 2024)
Surah Al-Fatihah, as the opening of the Al-Quran, contains a deep meaning that covers various aspects of faith, including Tauhid Rububiyah. This research aims to explore the interpretation of Tauhid Rububiyah in Surah Al-Fatihah using the ijmali interpretation methodology. Through analysis of the verses of Al-Fatihah, especially the second verse, "الْحَمْدُ لِلَّهِ رَبِّ الْعَالَمِينَ" (Praise be to Allah, the Lord of the worlds), this research reveals the meaning of the oneness of Allah as the Creator and Sustainer of the universe. This research also considers various perspectives from ulama in interpreting Tauhid Rububiyah in the context of Al-Fatihah. This research found that Surah Al-Fatihah explicitly emphasizes the oneness of Allah as Rabb, who has absolute power over everything. This is connected with various internal and external evidence, including other verses in the Koran and the hadith of the Prophet. The importance of understanding Tauhid Rububiyah through Surah Al-Fatihah lies in its practical implications in life. This encourages Muslims to recognize the oneness of Allah as Creator and Sustainer, thereby giving rise to feelings of gratitude, submission and obedience to Him. It is hoped that this research can contribute to a deeper understanding of Tauhid Rububiyah and its relevance in everyday life.